Dobór menedżerów do firm międzynarodowych działających w Polsce - wyniki badań empirycznych - Przytuła, Sylwia (Staffing of managers in international companies operating in Poland, 2006)
This article presents the results of the research project conducted in 34 international companies in Poland. On the basis of data received from companies belonging to the “triad models of management” which are Asian, American and European firms, the author presents the state of practice in staffing managers to these companies. This study shows the recruitment methods, selection and placement techniques for managerial positions in the international companies in Poland. The author indicates the crucial meaning of the cultural context of management because it determines the choice of recruitment tools with reference to this group of employees that worldwide operations and successful businesses depend on.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 258-265